Infografis : Pentingnya Dalam Pemberitaan (Studi Kasus Media Online Kumparan) - Maharani .; Sumaina Duku; Lilis Sukmawati (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This study aims to analyze the importance of using infographics in news reporting, using a case study of the online media Kumparan. The use of infographics is increasing along with the audience's need for concise, visual, and easy-to-understand information. This study uses a qualitative descriptive approach with data collection techniques through content observation, documentation, and literature studies. The results show that infographics in Kumparan play a significant role in clarifying data, increasing reader engagement, and helping convey complex information more simply. Furthermore, infographics have been proven to increase the visual appeal of news and strengthen the audience's understanding of the issues being reported. Thus, infographics have a significant contribution to the quality of information presentation and the effectiveness of communication in modern online media.